ChemInform Abstract: Copper(II)‐Catalyzed Enantioselective Hydrosilylation of Halo‐Substituted Alkyl Aryl and Heteroaryl Ketones: Asymmetric Synthesis of (R)‐Fluoxetine and (S)‐Duloxetine. Issue 27 (8th July 2014) - Zhou, Ji‐Ning; Fang, Qiang; Hu, Yi‐Hu; Yang, Li‐Yao; Wu, Fei‐Fei; Xie, Lin‐Jie; Wu, Jing; Li, Shijun
Abstract A series of chiral alcohols, e.g. compounds (II) and (IV), is prepared by enantioselective hydrosilylation of corresponding ketone precursors using cupric acetate and a P‐Phos ligand as catalytic system.